2005
DOI: 10.1080/00224490509552265
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of father‐son communication about sexuality

Abstract: Examining the factors that influence adolescents' sexual behaviors is crucial for understanding why they often engage in risky sexual behaviors. Using social cognitive theory, we examined predictors of father-son communication about sexuality. Fathers (N=155) of adolescent sons completed a survey measuring 12 variables, including self-efficacy and outcome expectations. We found that (a) son's pubertal development, father's sex-based values, father's education; father's communication with his father, outcome ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 30 publications
3
51
1
2
Order By: Relevance
“…Consistent with other studies (Lehr, et al, 2005, Tapia-Aguirre, et al 2004, parents in this study that had more education showed higher levels of sexual knowledge but not higher communication about sexual topics or comfort. Similarly, while fathers had higher levels of sexual knowledge, mothers perceived higher levels of sexual communication with their adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with other studies (Lehr, et al, 2005, Tapia-Aguirre, et al 2004, parents in this study that had more education showed higher levels of sexual knowledge but not higher communication about sexual topics or comfort. Similarly, while fathers had higher levels of sexual knowledge, mothers perceived higher levels of sexual communication with their adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have found parents play a fundamental role in the prevention of risky sexual behavior in their adolescent children (Blake, Smikin, Ledsky, Perkins, & Calabrese, 2001;Lehr, Demi, Dilorio & Facteau, 2005). However, the successful development of this role depends on how much sexual knowledge parents have and the way in which they communicate with their children about these issues (Blake et al, 2001;Lehr et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several common barriers to communication link directly to parental responsiveness, including embarrassment [17,23] or discomfort [21] in discussing sexual issues and apprehension about their children's response to such discussion [22,24]; lack of confidence in their own ability to communicate with their children about sexuality [25]; and lack of knowledge or skills to conduct such discussions [23]. Reciprocally, aspects of parental responsiveness are frequently found to be facilitators of communication, including confidence in one's ability to talk with children about sexual issues [25,26], and greater skill and comfort in communicating [27].…”
mentioning
confidence: 99%
“…sexuality) with their children (Gabb, 2004;Jordan, Price & Fitzgerald, 2000;Kakavoulis, 2001), especially fathers (Goldman and Bradley, 2004;Kirkman, Rosenthal & Feldman, 2003;Lefkowitz, Roma, Corona, Au & Sigman, 2000a;Lehr, Demi, Dilorio, & Facteau, 2005;Miller, Dilorio & Dudley, 2002). It has been suggested that parents feel unable to discuss these topics, such as sexuality, as they fear that they are not equipped with both the necessary skills and the knowledge to educate their children (WernerWilson & Fitzharris, 2001).…”
Section: Introductionmentioning
confidence: 99%